Incidence and economic burden of sarcoidosis in years 2011–2015 in Silesian voivodeship, Poland: Sarcoidosis – Poland - Niewiadomska, Ewa; Kowalska, Małgorzata; Skrzypek, Michał; Bocionek, Agata; Czech, Elżbieta (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
Background: Sarcoidosis is a rare, chronic systemic disease. Earlier data (2006-2010) suggest that the incidence of pulmonary sarcoidosis in Silesian voivodeship increased, however there is no current data on other clinical forms of the disease. Objectives: The aim of presented study was an analysis of the actual epidemiological situation of sarcoidosis with simultaneous estimation of treatment cost financed from public funds. Methods: Epidemiological descriptive study concerned registered cases of sarcoidosis diagnosed in adult inhabitants of the Silesian voivodeship in years 2011-2015. Secondary epidemiological data on the main diagnosis and co-morbidity were obtained from the National Health Fund (NFZ) database in Katowice. Territorial and temporal variability of standardized incidence rates were analysed with simultaneous estimation of treatment costs reimbursed from the state budget. Results: Pulmonary sarcoidosis was the most frequently registered clinical form of such disease in the Silesian voivodeship (65% of total cases). The highest number of cases was diagnosed in the age 35–54 years, frequently in men than in women. Significantly decrease of the standardized incidence of sarcoidosis noticed between 2011 and 2015 is related with observed lower number of total cases of pulmonary disease. Observed territorial variability of the sarcoidosis incidence requires future, well-planned studies. The annual average direct cost of sarcoidosis treatment is high and exceed 538 EUR per patient.Conclusions: It was confirmed that sarcoidosis in the Silesian Voivodeship is a rare disease, however reimbursed direct costs of treatment remains very high.